2006
DOI: 10.1038/sj.pcan.4500855
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the risk of long-term erectile, urinary and bowel symptoms resulting from prostate cancer treatment

Abstract: Reports on long-term complications resulting from treatment for localized prostate cancer are very inconsistent. In order to estimate the risks of long-term erectile dysfunction, urine symptoms and bowel symptoms following prostatectomy (RP), external conventional or conformal beam radiation (ERT or CRT) and brachytherapy (BRT), 98 papers from the PubMed and Cochrane Clinical Trial databases were selected, reviewed and critically evaluated. The majority of papers were institutionbased retrospective and prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 142 publications
1
17
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The rates of ED after conventional radiation therapy range from 40 to 65%, [22][23][24][25][26][27] and the rates of ED after brachytherapy range from 16 to 50%. 28 The true etiology of ED after radiation therapy remains controversial. Post-radiation ED has been postulated to involve damage to the proximal penile structures, such as the penile bulb, the neurovascular bundles and the local vascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The rates of ED after conventional radiation therapy range from 40 to 65%, [22][23][24][25][26][27] and the rates of ED after brachytherapy range from 16 to 50%. 28 The true etiology of ED after radiation therapy remains controversial. Post-radiation ED has been postulated to involve damage to the proximal penile structures, such as the penile bulb, the neurovascular bundles and the local vascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study found that the 5-year actuarial likelihood of developing a grade 3 urinary toxicity was significantly higher in the brachytherapy group compared with the 3-DCRT group [4]. A meta-analysis compared the risk of urinary symptoms after brachytherapy, external beam radiotherapy (EBRT), 3-DCRT, and prostatectomy for the treatment of prostate cancer [3]. When comparing randomized trials, the researchers found a 20% to 59% and 33% to 53% risk of minor urinary dysfunction (< RTOG grade 2) in the EBRT and 3-DCRT groups, respectively, and a 2% to 20% and 9% risk of major urinary toxicities (> RTOG grade 2) in the EBRT and 3-DCRT groups, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…Each method has its own complication profile and its unique voiding dysfunction characteristics [3][4][5]. To minimize urinary complications it is important to first understand the short-term and long-term anatomic and physiologic consequences of radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In these criteria, a radiation morbidity score of 2 or greater for the acute and longterm criteria would require medical management. To get an idea of the breadth of patients who will seek medical attention for urinary toxicities, a meta-analysis compared the risk of urinary symptoms after brachytherapy, external beam radiotherapy (EBRT), three-dimensional conformal radiation therapy, and prostatectomy for the treatment of prostate cancer [3]. When comparing randomized trials, the researchers found a 2% to 20% and 9% risk of major urinary toxicities (> Radiation Therapy Oncology Group grade 2) in the EBRT and three-dimensional conformal radiation therapy groups, respectively.…”
Section: Acute Versus Late Complicationsmentioning
confidence: 99%